Shifts in food quality for herbivorous consumer growth: multiple golden means in the life history - Bullejos, Francisco José (2014)
Consumer growth can be affected by imbalances between the nutrient content of the consumer and its food resource. Although ontogenetic-driven changes in animal composition are well documented, their potential consequences for the organism's sensitivity to food quality constraints have remained elusive. Here we show that the potential growth response of the copepod Mixodiaptomus laciniatus (as %RNA and RNA:DNA ratio) to the natural gradient of seston carbon (C) : nutrient ratio is unimodal and stage specific. Solution of the equation given by the first derivative function provided the optimum C : nutrient ratio for maximum stage-specific growth, which increased during ontogeny. The peakedness of the function indicated that animal vulnerability to suboptimal food quality decreased as juveniles reached adulthood. Consistent with these results, a field experiment demonstrated that potential consumer growth responded to variations in seston C : phosphorus ratio, and that early life stages were particularly vulnerable to suboptimal food quality.